Investigating climate change perceptions and behaviors from a microscopic perspective in four mountain villages in Taiwan - Chen, Ying-Ta; Lin, Jiunn-Cheng; Wang, Su-Fen; Wang, Pei-Jung (Frontiers in Environmental Science, 2025)
Formulating climate change adaptation strategies based on local perceptions and behaviors, especially in mountainous areas, is challenging for managers. This study aims to identify the risk perception, avoidance behaviors, and adjustment strategies of residents in different mountain villages within the same township. A census was conducted through questionnaire-based onsite surveys, collecting 302 responses from four mountain villages in the Shuilixi township of Nantou County. The results indicate that Han people perform significantly better than indigenous people in avoidance behavior and adaptation strategies due to better socio-economic conditions. Significant differences emerge among four groups: indigenous in high-risk areas, Han in high-risk areas, indigenous in low-risk areas, and Han in low-risk areas. Residents in low-risk areas, regardless of ethnicity, outperform those in high-risk areas in climate risk perception, avoidance behavior, and adaptation strategies. Respondents from different backgrounds (gender, age, income, occupation) in low-risk areas also fare better in these aspects. Notably, residents in high-risk areas exhibit lower actual avoidance behavior than their perceived behavior, possibly due to limitations in occupation, education, income, or available space. The study highlights significant differences in ethnic distribution and geographical features within small-scale villages in the upper Shuili stream area. It suggests that future research should compare towns and villages in different geographical locations for a broader understanding of population characteristics and that climate change disaster prevention planning should be considered on a village-by-village basis.